Acoustic properties of pistonphones at low frequencies in the presence of pressure leakage and heat conduction. (8th December 2015) - Zhang, Fan; He, Wen; He, Longbiao; Rong, Zuochao
Abstract: The wide concern on absolute pressure calibration of acoustic transducers at low frequencies prompts the development of the pistonphone method. At low frequencies, the acoustic properties of pistonphones are governed by the pressure leakage and the heat conduction effects. However, the traditional theory for these two effects applies a linear superposition of two independent correction models, which differs somewhat from their coupled effect at low frequencies. In this paper, acoustic properties of pistonphones at low frequencies in full consideration of the pressure leakage and heat conduction effects have been quantitatively studied, and the explicit expression for the generated sound pressure has been derived. With more practical significance, a coupled correction expression for these two effects of pistonphones has been derived. In allusion to two typical pistonphones, the NPL pistonphone and our developed infrasonic pistonphone, comparisons were done for the coupled correction expression and the traditional one, whose results reveal that the traditional one produces maximum insufficient errors of about 0.1 dB above the lower limiting frequencies of two pistonphones, while at lower frequencies, excessive correction errors with an explicit limit of about 3 dB are produced by the traditional expression. The coupled correction expression should be adopted in the absolute pressure calibration of acoustic transducers at low frequencies. Furthermore, it is found that the heat conduction effect takes a limiting deviation of about 3 dB for the pressure amplitude and a small phase difference as frequency decreases, while the pressure leakage effect remarkably drives the pressure amplitude to attenuate and the phase difference tends to be 90° as the frequency decreases. The pressure leakage effect plays a more important role on the low frequency property of pistonphones. Highlights: We model the pistonphone formula considering the leakage-conduction coupled effect. We model the leakage-conduction coupled correction formula of pistonphones. Insufficient correction error is avoided above lower frequency limit of pistonphones.